Feasibility, safety, and short-term outcome of totally thoracoscopic mitral valve procedure - Qin Jiang; Tao Yu; Keli Huang; Lihua Liu; Xiaoshen Zhang; Shengshou Hu (Journal of Cardiothoracic Surgery, 2018)
Abstract Background The totally thoracoscopic procedure for mitral valve (MV) disease is a minimally invasive method. We investigated the procedure’s feasibility, safety and effectiveness when it was performed by an experienced operator. Methods We retrospectively analysed 53 consecutive patients with MV disease treated between December 2014 and April 2017 by minimally invasive procedures. The procedures were performed on femoral artery-vein bypass through three 2–4 cm incisions, with one additional penetrating point on the right chest wall under totally thoracoscopic visual guidance and surveillance of transoesophageal echocardiography. Results Two patients who underwent intraoperative conversion to sternotomy were excluded due to indivisible pleural cavity adhesion. Of the others (38 female patients, average age, 49 ± 14 years, left ventricular ejection fraction, 59 ± 7%), 34 received MV replacement for rheumatic mitral lesions, which was redone for one patient after the discovery of serious paravalvular leakage, 17 received MV repair for mitral regurgitation (with 4 secondary to atrial septum defect, 2 diagnosed with left atrial myxoma, and 2 redone for mitral valve replacement due to repair failure), 28 received additional tricuspid valvuloplasty, and one patient received a Warden procedure. The cardiopulmonary bypass and aortic cross clamp times were 144 ± 39 min and 80 ± 22 min, respectively. Postoperational chest tube drainage in the first 48 h was 346 ± 316 ml. The ventilation time and intensive care unit stay length were 11 ± 11 h and 23 ± 2 h, respectively. One patient died of disseminated intravascular coagulation and prosthesis thrombosis with fear of anticoagulation-related bleeding. Conclusions The totally thoracoscopic procedure on mitral valves by an experienced surgeon is technically feasible, safe, effective and worthy of widespread adoption in clinical practice.